Analisis Daya Saing Kopi Indonesia dan Vietnam di Pasar Internasional - Willdan, Meylinda; Santoso, Siswanto Imam; Nurfadhilah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Indonesia and Vietnam are leading global coffee exporters, both ASEAN members. Despite Vietnam's smaller land area, it exports more coffee, ranking second globally, while Indonesia is fourth. This research aims to: 1) analyze the comparative and competitive advantage of Indonesian and Vietnamese coffee; and 2) identify competitive advantage factors using Porter's Diamond Model. Data analysis Methods included Revealed Comparative Advantage (RCA) for comparative advantage, Trade Specialization Index (TSI) for competitive advantage, and Porter's Diamond Model for determining factors. The research results for the period 2000-2023 show that: 1) the average RCA value for coffee from 2000-2023 for Indonesia was 5.5 and  Vietnam was 22.7, and the average TSI value for Indonesian coffee was 0.91 and for Vietnam was 0.96; 2) Based on Porter's Diamond Model analysis, Indonesia's factor conditions are indicated by vast agricultural land, diverse agroclimates, abundant labor, and infrastructure development, while Vietnam's are indicated by land efficiency, technical training, access to capital, and developing infrastructure. Indonesia's domestic demand conditions are rapidly developing, while Vietnam focuses on exports. Related and supporting industries are indicated by the development of coffee raw materials, namely seeds, in each country. Both Indonesia and Vietnam have complex firm strategy, structure, and rivalry, ranging from small-scale farmers to large companies.